Development and characterization of polyethersulfone/TiO2 mixed matrix membranes for CO2/CH4 separation - Galaleldin, S. (American Institute of Physics Inc., 2017)
In this study, mixed matrix membranes comprised of polyethersulfone as the bulk polymer phase and titanium dioxide (TiO2) nanoparticles as the inorganic discontinuous phase were prepared for CO2/CH4 separation. Membranes were synthesized at filler loading of 0, 5, 10 and 15 wt via dry phase inversion method. Morphology, chemical bonding and thermal characteristics of membranes were scrutinized utilizing different techniques, namely: Field Emission Scanning Electron Microscopy (FESEM), Fourier Transform InfraRed (FTIR) spectra and Thermogravimetric analysis (TGA) respectively. Membranes gas separation performance was evaluated for CO2 and CH4 gases at 4 bar feed pressure. The highest separation performance was achieved by mixed matrix membrane (MMM) at 5 loading of TiO2. © 2017 Author(s).